Simulações em laboratório de escoamentos em meios estratificados - Demarco, Giuliano (2013)
In the present thesis, two distinct scientific problem in fluid mechanics are studied using laboratory observation techniques. In the first of them, a tank was used to simulate microburst propagation. In the experimental set-up, the flow was driven by combined impinging jet and density perturbations forcing with the aim of determining their relative influence on the overall microburst behaviour and, in particular, the initiation and structural evolution of the resulting vortex. These results were compared with those reported in previous simulation works. Such comparisons showed that the laboratory model may satisfactorily reproduce relevant aspects of a microburst. An expression for the characteristic microburst propagation velocity was derived, accounting for the combined effects of forced velocity and flotation forces generated by the density difference. The vortex structure is largely affected by the forcing type. The succession of vortex is best defined when a large density perturbation is combined with a weak jet impingement. The opposite configuration causes a main vortex to be succeeded by a wake where vortex structures are not clearly defined. In the second part, experiments were conducted in a wind tunnel above a cooled surface with the aim of determining the influence of the thermal stratification on turbulence-related quantities. The experimental apparatus consists of an aluminum plate inserted at the bottom surface of the test section, which is then cooled until 5ºC, so that a stably stratified surface is formed. As wind speeds increase, such a stable layer is soon destroyed. Data show that quantities such as temperature, variances, dissipation rates and turbulent fluxes are substantially reduced when a stratification is present. On the other hand, third and fourth order statistical moments, as well as the mean wind speed are very slightly affected by the stratification.